Occurrence of Cu2+ microorganisms on Antarctic island Galindez - Tashyreva, G. O.; Matveewa, N. A.; Tashyrev, O. B. (Ukrainian Antarctic Journal, 2006)
Copper resistance of Antarctic microbial communities selected from different samples (sediments, plants etc.) was investigated at Cu2+ concentrations of 5, 25, 100 ppm. It was shown that all samples contained Cu2+-resistant microorganisms in large amounts, about 104–107 CFU/g of sample. There were found 15 morphological types of bacteria, 3 types of actinomycetes, 5 types of fungi. For microorganisms from most samples (65%), 100 ppm Cu2+ did not show an inhibitory effect.